(untitled) (Research, Society and Development, 2023)
Objective: to identify in the scientific literature of the last 10 years (2013-2022), the main understandings about the TPACK model in relation to educational technologies in teacher training. Methodology: This is a systematic literature review, data collection took place in January 2023, via the University of Lisbon search service in Portugal, directed to the EBSCO Discovery Service (EDS) meta-database. Two search equations were used, one in Portuguese and the other in English. Results: initially 162 studies were identified, subjected to consensus analysis by two experts in the area of technologies in education and teacher training, identifying nine articles in accordance with the eligibility criteria. As for the temporality of the publications, we observed a single article published in the year 2022, the highest frequency of publication was in the period from 2016 to 2022 with seven studies and the period from 2012 to 2015 with two publications. Conclusion: Considering the teacher’s formative process strongly tensioned by the need to adopt and integrate digital technologies in the most diverse teaching and learning spaces, all this greatly accentuated by the pandemic crisis of COVID-19. The scientific literature analyzed points to the TPACK model as a teaching axis that appropriates concepts about the use of educational technologies, structured on recent knowledge in the context of teacher training. However, with gaps to be answered in future investigations.